Research on Oil Adsorption Capacity of Carbonized Material Derived from Agricultural by-product (Corn Cob, Corn Stalk, Rice Husk) Using in Oily Wastewater Treatment - Ha, Nguyen Thanh; Cat, Le Van; Anh, Pham Vy; Lien, Tran Thi Thuy (VNU Journal of Science: Natural Sciences and Technology; Vol 32 No 3, 2016)
Abstract: Oily wastewater discharged from machinery producing, mining, storage service, marine transporting... is one of the polluting sources to receiving waterbody. Adsorption onto carbonized material derived from agricultural by-products are proved to be the promising treatment for this type of wastewater. Experiments implemented with the agro-wastes including: corn cob, corn stalk and rice husk with carbonizing temperature of 300-600 o C and retention time of 1-3h. According to the results of all carbonized materials, the decrease of oil adsorption accosiated with higher pyrolysis temperature, as well as longer retention duration. Under the same carbonizing conditions, the carbon derived from corn stalk have the higher adsorption capacity. The highest oil sorption capacity of 6.4 g/g is of corn stalk derived carbon with temperature of 300 o C, retention time of 1h; while the lowest one of 2.33 g/g is of material derived corn cob with temperature of 600 o C, 1h. The oil adsorption capacity is closely related to the porosity and oleophilic groups on the surface of the material. The results indicated that materials made from agricultural by-products, corn stalk in particular, are promising for oily wastewater treatment.  Keywords: Corn cob, corn stalk, rice husk, oily wastewater.